Behavior and budget of dissolved uranium in the lower reaches of the Yellow (Huanghe) River: Impact of Water–Sediment Regulation Scheme. (October 2015) - Sui, Juanjuan; Yu, Zhigang; Jiang, Xueyan; Xu, Bochao
Highlights: Behavior of dissolved U in the lower reaches of Yellow (Huanghe) River influenced by the WSRS has been discussed. Budget of dissolved uranium during the WSRS has been calculated. The geochemical and environmental implications of the WSRS have been discussed. Abstract: The Water–Sediment Regulation Scheme (WSRS) is an important water conservancy project in the Yellow River basin, which is usually operated annually from June to July to control water and sediment release from the Xiaolangdi Reservoir in the middle reaches. As a greatly concentrated period of delivering terrigenous materials from the Yellow River to the sea, the WSRS can serve as a natural laboratory to examine the geochemical behavior of elements during their transport along the river. Uranium isotopes ( 234 U and 238 U) were measured in Yellow River waters at stations Xiaolangdi (located in the middle reaches of the Yellow River) and Lijin (the last hydrologic station near the Yellow River estuary) during the WSRS 2012. Compared with station Xiaolangdi, dissolved uranium concentration at station Lijin was markedly higher, showing a significant impact from the WSRS. Budget calculation for dissolved uranium during the WSRS indicated that two major sources of new added dissolved uranium in the section of the Yellow River between Xiaolangdi and Lijin: suspended particles (46%) and porewater of bottom sediment (45%). The flux of dissolved uranium from the Yellow River to the sea was estimated to be 2.40 × 10 7 g during the WSRS 2012.